MAREK'S DISEASE: THE NEVER ENDING CHALLENGE –A REVIEW - SMITHA SUDHAKAR,; Dr. A. JAYAKUMARAN NAIR, (International Journal of Pharma and Bio Sciences, 2013)
Marek's disease virus is a highly oncogenic alpha-herpesvirus that induces Marek's disease, a lymphomatous disease in poultry which accounts for the huge economic loss every year. The virus has been an ever evolving strain with different pathotypes causing much concern because of possible interspecies transfer to humans. The existing vaccines may drive the pathogen to more and more virulence .So it is very particular that new recombinant vaccines or improved vaccines based on Herpes Virus of Turkey’s, that can hinder viral replication and egression, should be developed. Marek’s virus serves as a model for herpes virus induced cancer studies outside humans and when disarmed the virus itself is assumed to be the best vaccine against cancer of Herpes Simplex Viral origin.